Uncovering transcriptional dark matter via gene annotation independent single-cell RNA sequencing analysis - Michael F. Z. Wang (Nature Portfolio, 2021)
Conventional single-cell RNA sequencing analysis rely on genome annotations that may be incomplete or inaccurate especially for understudied organisms. Here the authors present a bioinformatic tool that leverages single-cell data to uncover biologically relevant transcripts beyond the best available genome annotation.